Diretrizes para o desenvolvimento de processos de autoavaliação de cursos de graduação - Santos, João Timóteo de Los (2018)
This research work, developed in the Professional Master's Program of the Graduate Program in Public Policies and Educational Management, Federal University of Santa Maria, in the line of research concerning pedagogical management and educational contexts, under the guidance of the teacher Dr. Maria Eliza Rosa Gama. It presents as general topic of research the in-depth study with respect to the evaluation of undergraduate courses, having as specific theme the study focused on the guidelines for the development of self-assessment processes of undergraduate courses developed by the Federal University of Pampa (Unipampa), in the course degree in Administration, from the campus of Santana do Livramento - RS. The focus of the research is on the expectations of the internal community of the institution to compose a process of self-assessment for the undergraduate courses, aiming at understanding the demands for the institutionalization of the management processes of self-assessment of undergraduate courses at Unipampa. In order to arrive at an answer, three questions were unfolded: What conceptions about the institutionalization of evaluation processes and self-assessment of undergraduate courses reveal the management practices at Unipampa? How are the Self-Assessment processes performed by Unipampa characterized? and what implications does the Self-Assessment have on the organization and operation of the Undergraduate Course? In order to arrive at the answers of these questions, data collection tools and specific query sources were defined for each type of questioning. The analysis of these answers provided support to solve a fourth question, which refers to What possibilities for the institutional management of course self-assessment processes are evidenced? Once this last question was solved, it was possible to elaborate the final product of the work, which includes a set of guidelines to assist the management of a self-assessment process for the undergraduate courses of the Institution that meets the expectations of the academic community